PENENTUAN PREMI DAN CADANGAN PADA ASURANSI PENDIDIKAN DENGAN MEMERHATIKAN PELUANG HIDUP ANAK - DEWI, NI LUH DE SISKA SARI; WIDANA, I NYOMAN; JAYANEGARA, KETUT (E-Jurnal Matematika; Vol 10 No 4 (2021)DO - 10.24843/MTK.2021.v10.i04.p350, 2021)
Education insurance provides services in the field of education. In education insurance, the insured not only gets protection benefits but also education funds. These benefits will be received if they have paid premiums. Insurance companies also need to set the exact amount of policy value. The purpose of this study is to determine the premium and policy value of education insurance by taking into account the child's life chances. In this study, used secondary data from the 2011 Indonesian Mortality Table and illustrated data in the form of education fund data. Premium is obtained using the equivalence principle and policy value is obtained using the prospective method. In the calculation of premiums and policy values for education insurance premiums by taking into account the child's life chances, modifications are made, the amount of education funds multiplied by the child's life chances. The results given in this study are the amount of education insurance premium by taking into account the child's life chances is Rp 6.946.456,00. Policy value increases during the disbursement of education funds and decreases at the end of coverage.